Family planning utilization among postpartum women in the Bule Hora District, southern Ethiopia - Sirage, Nurye; Desalegn, Zewuditu; Wako, Wako Golicha; Yimer, Ali; Bizuneh, Fassikaw Kebede; Feleke, Sefineh Fenta; Yesuf, Adem; Beyene, Belda Negesa (Frontiers in Global Women's Health, 2024)
BackgroundContraception use remains low in Ethiopia, particularly within the first year after childbirth. While some women might have medical conditions that limit their contraceptive options, the primary obstacle to wider family planning adoption is not a specific health problem. Instead, it is the lack of equitable access to high-quality family planning services. This barrier significantly hinders women's ability to make informed decisions about their reproductive health. This study examines postpartum family planning utilization and its associated factors among postpartum mothers in the Bule Hora District.MethodsWe conducted a community-based cross-sectional study. A multistage sampling technique was employed to recruit a total of 630 women who had given birth. To collect the data, structured, standardized, and pretested questionnaires were used, and the collected data were coded and entered into Epi-data version 4.6. The data were analyzed using SPSS version 25. Both bivariable and multivariable logistic regressions were used to identify factors associated with postpartum family planning utilization.ResultsThe study found that 71.3% of women utilized postpartum family planning. Significant associations were found between postpartum family planning utilization and various factors, including counseling on family planning during pregnancy [adjusted odds ratio (AOR) = 1.79, 95% confidence interval (CI) 1.61–2.82], delivery (AOR = 2.62, 95% CI 1.56–4.38), and the postpartum period (AOR = 2.71, 95% CI 1.75–4.21). Women who resumed sexual activity after birth (AOR = 1.92, 95% CI 1.25–2.96), and who had at least four antenatal care visits (AOR = 3.09, 95% CI 1.61–5.92) were also more likely to use postpartum family planning. Women with grand multiparity were 69% less likely to use family planning methods than primiparous women (AOR = 0.31, 95% CI 0.13–0.73).ConclusionPostpartum family planning use in this study was higher than the national average. Factors such as parity; counseling during the pregnancy, delivery, and postpartum periods; and early resumption of sexual activity were linked to increased contraceptive use. These findings suggest that enhanced counseling during antenatal, delivery, and postnatal care could significantly increase contraceptive use.